The Effect of Elsa Speak Application on Students’ English Pronunciation Development - Adawiah, Rabiatul; Muliati, A.; Samtidar, Samtidar (Journal of Excellence in English Language Education, 2024)
This research aimed to determine the effect of the ELSA Speak application on students' English pronunciation development. The research design was pre-experimental. This research was taken place at UPT SMP Negeri 1 Sungguminasa. The participants of this research were the students of the 8A Multimedia, and the total population was 35 students. The researchers used a quantitative case study with a purposive sampling technique to select the participants. Based on the pre-test and post-test results, the researchers found that the ELSA Speak application was effective in developing students' English pronunciation. Based on the study's results, it is known that the post-test mean score (83.49) is greater than the pre-test means score (77.20). Based on the pre-test to post-test, the score of N-gain (normalized gain) is used to measure the improvement of science process skills and cognitive learning outcomes between before and after treatment is 5.5. This indicates that the ELSA Speak Application is quite effective in improving students' English pronunciation to be better.